Libraries and Facilitation of Public Access to Information in Nigerian Society - Oluwayinka,Solanke, Ngozi P.Osuchukwnu (IJoLIS, 2024)
Purpose: This study examined the level of liberaries ' involvement in facilitating public access to information, strategies used, chalenges faced, and best practices used.